The effect of time delay for synchronisation suppression in neuronal networks. (November 2022) - Hansen, Matheus; Protachevicz, Paulo R.; Iarosz, Kelly C.; Caldas, Iberê L.; Batista, Antonio M.; Macau, Elbert E.N.
Abstract: We study the time delay in the synaptic conductance for suppression of spike synchronisation in a random network of Hodgkin–Huxley neurons coupled by means of chemical synapses. In the first part, we examine in detail how the time delay acts over the network during the synchronised and desynchronised neuronal activities. We observe a relation between the neuronal dynamics and the synaptic conductance distributions. We find parameter values in which the time delay has high effectiveness in promoting the suppression of spike synchronisation. In the second part, we analyse how the delayed neuronal networks react when pulsed inputs with different profiles (periodic, random, and mixed) are applied to the neurons. We show the main parameters responsible for inducing or not synchronous neuronal oscillations in delayed networks. Highlights: We study the effects of time delay in the synaptic conductance. The time delay has high effectiveness in promoting the suppression of synchronisation. Interventions that change the time of neuronal transmission can suppress synchronisation.